2020
DOI: 10.1136/heartjnl-2019-316227
|View full text |Cite|
|
Sign up to set email alerts
|

Animation-supported consent for urgent angiography and angioplasty: a service improvement initiative

Abstract: ObjectivePatient understanding of angiography and angioplasty is often incomplete at the time of consent. Language barriers and time constraints are significant obstacles, particularly in the urgent setting. We introduced digital animations to support consent and assessed the effect on patient understanding.MethodsMulti-language animations explaining angiography and angioplasty (www.explainmyprocedure.com/heart) were introduced at nine district hospitals for patients with acute coronary syndrome before urgent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous work has shown that use of Explain my Procedure multi-language animations improved patient and relative-reported understanding in other disciplines, including interventional cardiology [ 7 , 8 ], radiology [ 11 ], electrophysiology [ 12 ] and intensive care medicine [ 13 ]. The present work extends the benefits of this approach into a general surgical setting for one of the most commonly performed surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that use of Explain my Procedure multi-language animations improved patient and relative-reported understanding in other disciplines, including interventional cardiology [ 7 , 8 ], radiology [ 11 ], electrophysiology [ 12 ] and intensive care medicine [ 13 ]. The present work extends the benefits of this approach into a general surgical setting for one of the most commonly performed surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia resources such as animation-supported consent have been effectively implemented to improve patients’ understanding before consent and free up time to focus on material concerns. In angiography and angioplasty, digital animations have been introduced into the elective and urgent patient pathways [ 7 , 8 ]. The animations describe the procedure, its intended benefits, possible risks, and alternatives to the procedure in multiple languages that patients can choose; and approach consistent with GMC guidance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] Introduction of digital animations in a network of 9 hospitals lead to a 3-fold increase in understanding of urgent angiography and a 10-fold increase in appreciation of risks before consent. 7 The present work, using multi-language animations, extends this approach to supporting families of patients on intensive care, rather than patients themselves. The striking differences in reported understanding between the animation and no animation groups, particularly in understanding what mechanical ventilation involves (94% v 15%) and appreciation of risk (84% v 0%) quantifies the benefit but also highlights the sizeable gap in understanding that exists and that has, no doubt, been worsened by the COVID-19 pandemic restrictions on visiting and communication.…”
Section: Discussionmentioning
confidence: 99%
“…5 Multi-language animations describing the benefits, risks and alternatives of commonly performed medical and surgical procedures have been shown to substantially improve patient understanding before consent, both in the elective and urgent patient pathway. 6,7 Animations describing ICU and the treatments offered were developed and translated into 5 different languages (Explain my Procedure Ltd) as part of a UK Government Scheme to support the COVID-19 response and were endorsed by the Intensive Care Society.…”
Section: Introductionmentioning
confidence: 99%